Gaia: The Astrometry Revolution. Issue Volume 10:Issue S314(2015) (November 2015) - Sozzetti, A.; Bonavita, M.; Desidera, S.; Gratton, R.; Lattanzi, M. G.
Abstract: The power of micro-arcsecond (μas) astrometry is about to be unleashed. ESA's Gaia mission, now headed towards the end of the first year of routine science operations, will soon fulfil its promise for revolutionary science in countless aspects of Galactic astronomy and astrophysics. The potential of Gaia position measurements for important contributions to the astrophysics of planetary systems is huge. We focus here on the expectations for detection and improved characterization of 'young' planetary systems in the neighborhood of the Sun using a combination of Gaia μas astrometry and direct imaging techniques.